Confined Blood Chimerism in Monochorionic Dizygotic Twins Conceived Spontaneously - Takashi Kanda; Masanobu Ogawa; Kazuo Sato (Thieme Medical Publishers, Inc., 2013)
Abstract Traditionally, monochorionicity has been regarded as synonymous with monozygosity. However, several recent cases of monochorionic dizygotic twins have shown that monochorionic twins can be dizygous. We report a rare case of monochorionic diamnionic, gender-discordant twins who were conceived spontaneously. Initially, a monochorionic placenta was diagnosed by ultrasonography at 8 weeks of gestation and then confirmed by pathology after delivery. The twins had different genders. A comparison of cytogenetic analyses using peripheral blood lymphocytes and skin fibroblasts revealed that chimerism was confined to blood cells. We have experienced two cases of monochorionic dizygotic twins since 2003. These cases suggest that monochorionic dizygotic twins are not as rare as previously thought.